Reactive agility tests - Review and practical applications - Inglis, P.; Bird, S. P. (Journal of Australian Strength and Conditioning, 2016)
Agility is defined as a rapid whole-body movement with change of direction or speed in response to a stimulus. However, traditional agility tests do not address this definition and are pre-planned with no stimulus. In response to this, studies have been conducted to develop a new agility test that incorporates a sport-specific stimulus. The aim of this review was to summarize the literature on reactive agility tests and provide coaches with recommendations on the best way to test and develop agility in athletes. A literature search was conducted to find agility tests that used a sport-specific stimulus and tested higher and lesser-skilled athletes. Ten articles were identified that meet the criteria for inclusion with half of the studies incorporating a video based stimulus while the other half used a tester as the stimulus. It was found that reactive agility tests were a valid and reliable method of testing agility compared to traditional pre-planned agility tests. Reactive agility tests can also be used as a training drill to improve an athlete`s perceptual and response times by using a sport specific stimulus while pre-planned agility drills may not.